Does light touch cluster policy work? - Nathan, Max (IZA - Institute of Labor Economics, 2019)
Despite academic scepticism, cluster policies remain popular with policymakers. This paper evaluates the causal impact of a flagship UK technology cluster programme. I build a simple framework and identify effects using difference-in-differences and synthetic controls on rich microdata. I further test for timing, cross-space variation, scaling and churn channels. The policy grew and densified the cluster, but has had more mixed effects on tech firm productivity. I also find most policy
10419/207456
Keywords: Graue Literatur; cities; clusters; technology; economic development; synthetic controls